Prevention of hypoparathyroidism with the use of calcium-rich foods in the total thyroidectomy pre-operative period - Segal, Marcelo Jacques; De Aquino, Jose Luis Braga; Merhi, Vania Aparecida Leandro; De Camargo, Jose Gonzaga Teixeira; Pizzinato, Paula Srebernich; Ramos, Joao Paulo Zenun; Delatti, Fernando De Almeida; Rocha, Felipe Couto Ferreira; Ferruccio, Aline Akel (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: Transient hypocalcemia after total thyroidectomy (TT) is a common surgical complication. Authors used calcium supplements in different doses and periods, mainly after TT to try to avoid hypocalcemia. Indistinct use has been challenged due to complications. Currently, the risk of hypocalcemia was assessed by measuring parathormone (PTH) after TT; however, without a consensus on the best time and amount to consider. The objectives of this study were to evaluate the incidence of hypoparathyroidism with the use of calcium-rich foods in the pre-operative period of TT, followed by a measurement of PTH performed 12 hours after such procedure Methods: A preliminary study with 31 patients earmarked for TT. Patients were divided into two groups: (A) without calcium-rich foods intake in the TT pre-operative period; and (B) with the intake of calcium-rich foods, in the TT pre-operative period. These foods composing different menus have been suggested, based on the need for daily calcium intake, according to the age group and nutritional data of the Dietary reference intake (DRI). Beginning of the use of these foods has been standardized as being seven days before surgery, due to the slower calcium intestinal absorption process. Results: Group B, when compared to A, showed a significant difference between PTH values, before and after surgery (p value <0.001). Conclusions: Calcium-rich foods intake in the conditions reported may be associated with lower rates of hypoparathyroidism.